Letter : 14th of April Fund - Cook, James
034-0020-001 Fife, Clackmannan and Kinross Miners Union. James Cook J.P. General Secretary James Potter, J.P. Compenstion Secretary P. Henderson, J.P. Disputes Secretary P. Ness, J.P. Organising Secretary Telephone No. 400 Victoria Street, Dunfermline. 4th June, 1942. In reply quote Ref JC/DSS. Dear Sir, 14th of April Fund. The above question was dealt with by my Standing Committee at their recent meeting and I was instructed to write you and to ask if you could give me any information regarding the above Fund which is supposed to represent Spanish Youth in Great Britain. The idea contained in the circular I received was that the authors were endeavouring to raise a fund to send parcels of food tobacco and soap to each of the Spaniards in the Concentration Camps of France and Africa. Contributions were to be sent to Mr Faustino Gayel, Treasurer of Spanish Youth, Hogar Espanol, 22 Inverness Terrace, London W.2. I was instructed to make enquiries into this matter before my committee decided whether or not a grant to this body should be recommended to our members and I am writing you in the hope that you may be able to give me some enlightenment on the matter. I shall be glad to hear from you at your convenience. Yours faithfully James Cook Sir Walter Citrine British Trade Union Congress, Transport House, Smith Square, LONDON. 292/946/34/20